2021
DOI: 10.1111/jcpt.13375
|View full text |Cite
|
Sign up to set email alerts
|

B vitamins as a treatment for diabetic pain and neuropathy

Abstract: What is known and objective: B vitamin therapy is a common treatment for diabetic pain and neuropathy, yet its use remains controversial in patients lacking B vitamin deficiencies. The aim of this review was to summarize the current evidence for the efficacy of B vitamin therapy in diabetic patients with neuropathy. Comment:We screened the English literature for clinical studies evaluating B vitamins as a therapy for pain and neuropathy in diabetic patients. We selected 43 relevant studies for qualitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
6
0
6
Order By: Relevance
“…Furthermore, the previous studies on the effect of vitamin B6 supplementation in other types of pain have implied the controversial results [ 26 ]. They do not appear to be comparable with the results of our study in FM because the pain mechanisms in these conditions are different from FM etiopathogenesis and represent a more homogenous nature in each condition rather than FM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the previous studies on the effect of vitamin B6 supplementation in other types of pain have implied the controversial results [ 26 ]. They do not appear to be comparable with the results of our study in FM because the pain mechanisms in these conditions are different from FM etiopathogenesis and represent a more homogenous nature in each condition rather than FM.…”
Section: Discussionmentioning
confidence: 99%
“…Sadeghi et al showed that 80 mg per day of pyridoxine attenuate the severity and duration of migraine headaches [12]. While some preclinical studies on rats showed the attenuated thalamic evoked nociceptive burst discharge and increased pain threshold, some clinical trials displayed that vitamin B6 monotherapy did not influence diabetic pain and neuropathy [13,25,26]. Ghavidel-Parsa et al BMC Musculoskeletal Disorders (2022) 23:664…”
Section: Discussionmentioning
confidence: 99%
“…In a review including 5 studies with a total of 348 participants, the evidence on the effects of B vitamins in diabetic polyneuropathy was uncertain [26]. Two reviews [27,28] concluded that vitamins B1, B6 and B12 may have an important role in nerve regeneration with clear disease-modifying mechanisms, but larger RCTs are required for longer periods are needed before these are included in official guidelines.…”
Section: Vitamins Of B-complexmentioning
confidence: 99%
“…Altogether, it has recently been concluded that the evidence for favorable effects of B vitamins in diabetic neuropathy and neuropathic pain shows substantive heterogeneity with respect to study designs and reported outcomes, highlighting the need for larger, placebo-controlled studies [ 92 ].…”
Section: Diabetic Neuropathymentioning
confidence: 99%